FACTORS INFLUENCING CITIZEN SATISFACTION IN GETTING PUBLIC SERVICE (CASE STUDY: THE SERVICE USER OF THE INVESTMENT AND ONE STOP SERVICE AGENCY OF TANAH BUMBU REGENCY IN 2018) - Iqbal, Muhammad; Mahbubah, Indriani; Akbar, Ali; Elianda, Yunita (Universitas Gorontalo, 2020)
The present study explained factors influencing citizen satisfaction service in the Investment and One-Stop Service Agency of Tanah Bumbu Regency. In particular, this research analyses the level of citizen satisfaction and the extent to which Awareness, Rules, Organizational, Income, Skill-Ability, and Service Facility Factor influence Citizen Satisfaction. This study uses a mixed methodology with a sequential explanatory strategy. Using the incidental sampling with Slovin's Formula to calculate the number of samples is 93 respondents. The quantitative data were analyzed by the SmartPLS 3.0 program. The findings showed that the level of citizen satisfaction is included in the category